Trapezium Bone Density—A Comparison of Measurements by DXA and CT - Breddam Mosegaard, Sebastian (J Funct Biomater, 2018)
Bone density may influence the primary fixation of cementless implants, and poor bone density may increase the risk of implant failure. Before deciding on using total joint replacement as treatment in osteoarthritis of the trapeziometacarpal joint, it is valuable to determine the trapezium bone density. The aim of this study was to: (1) determine the correlation between measurements of bone mineral density of the trapezium obtained by dual-energy X-ray absorptiometry (DXA) scans by a circumference method and a new inner-ellipse method; and (2) to compare those to measurements of bone density obtained by computerized tomography (CT)-scans in Hounsfield units (HU). We included 71 hands from 59 patients with a mean age of 59 years (43–77). All patients had Eaton–Glickel stage II–IV trapeziometacarpal (TM) joint osteoarthritis, were under evaluation for trapeziometacarpal total joint replacement, and underwent DXA and CT wrist scans. There was an excellent correlation (r = 0.94) between DXA bone mineral density measures using the circumference and the inner-ellipse method. There was a moderate correlation between bone density measures obtained by DXA- and CT-scans with (r = 0.49) for the circumference method, and (r = 0.55) for the inner-ellipse method. DXA may be used in pre-operative evaluation of the trapezium bone quality, and the simpler DXA inner-ellipse measurement method can replace the DXA circumference method in estimation of bone density of the trapezium.